Performance of CIP potato (Solanum tuberosum) clones for early maturity in subtropical region of Haryana - Pandey, P.; Arya, S.; Kadian, M.S.; Rani, D. (Indian Council of Agricultural Research, 2023)
Research experiments were carried out with six promising potato clones of International Potato Center (CIP) compared with four recommended varieties of Central Potato Research Institute (CPRI) as checks with the objective to identify high yielding, short duration variety suitable for rice-wheat cropping system of subtropical region of Haryana. The trials were conducted at Potato Technology Center, Karnal during rabi season of two consecutive years, viz. 2018-19 and 2019-20 under Rastriya Krishi Vikas Yojna Project. The experiments were laid out in randomized block design with three replications. All the cultural practices were followed with scientific management. Dehaulming was done after 75 days of planting. Physical characters of tubers like skin colour, flesh colour, tuber shape and eye depth were observed. Data related to vegetative growth and yield was recorded, pooled and statistically analyzed. It was observed from the data that the maximum plant vigour was recorded in cultivar Kufri Lima however, highest marketable and total tuber yield was recorded in a red skinned CIP clone CIP392797.22. This variety might be selected as a candidate variety fit for rice-wheat cropping system.